Using biomarkers in acute medicine to prevent hearing loss: should this require specific consent? - Coulson-Smith, Peta (Journal of medical ethics, 2020)
In this round table response, we discuss some of the problems inherent in insisting on specific consent for an activity that needs to happen rapidly as part of a package of care. The Human Tissue Authority (the UK regulator for human tissue and organs) consider that specific consent is mandatory to assess which antibiotics are appropriate on the neonatal unit, but this insistence may actually limit the autonomy which consent aims to promote. While genetic testing to determine which child will react adversely to particular antibiotics has been available clinically for several years, the research proposed here is to assess whether improving the speed of testing allows decisions to be made before treatment starts. Insisting on specific consent before this activity can take place is likely to delay appropriate care in some cases.On admission to the neonatal unit, the unwell infant is routinely subjected to a range of investigations and treatments.A person with parental responsibility will usually be asked to provide consent to undertake treatments for children who do not have capacity to give consent themselves.1 For the acutely unwell child, consent will usually be sought for a package of care: the urgent nature of neonatal medicine often requires clinicians to make many decisions without explicit consent. Doctors must always act in a child’s best interests: their decisions need to protect the health and well-being of a child and hold the child’s welfare paramount in accordance with the Children Act (1989) and General Medical Council (GMC) guidelines.1 2 Thus, for example, ventilation might be initiated, sedation provided, antibiotics commenced or diagnostic investigations requested without separate consent conversations or …